Cardiorenal disease development under chronic renin–angiotensin–aldosterone system suppression - Sarafidis, Pantelis A; Ruilope, Luis M (Journal of the renin-angiotensin-aldosterone system, 2012)
Drugs suppressing the renin-angiotensin-aldosterone system (RAAS) are now widely used to treat patients all along the cardiorenal continuum. It supposes that many patients, in particular those with arterial hypertension are treated with converting-enzyme inhibitors and angiotensin receptor blockers for years during which the development and prograssion of cardiorenal disease can be observed. The meaning of this progression in the presence of RAAS suppression requires to be clarified and to be treated in order to diminish the velocity of progression of cardiorenal disease.